FON: FROM START TO FINISH - Pakuliak, L. K.; Andruk, V. M.; Golovnia, V. V.; Shatokhina, S. V.; Yizhakevych, O. M.; Ivanov, G. A.; Yatsenko, A. I.; Sergeeva, T. P. (Одеські астрономічні публікації, 2016)
Almost 40-year history of FON project ended with the creation of the whole northern sky catalog of objects down to B ≤16.5m. The idea of 4-fold overlapping of the northern sky with 6 wide-field astrographs has not been realized in full. For historical reasons it has been transformed into the 2-fold overlapping observational program of MAO NAS ofUkraine, resulted in three versions of the multimillion catalog of positions, proper motions, and B-magnitudes of stars. The first version of 1.2 million stars had been finished before the 2000s and is based on the AC object list. The measurements of plates were made by automatic measuring complex PARSEC, specially developed for massive photographic reviews. As the input list was limited by AC objects, the most part of stars on the FON plates remained unmeasured. Principles of workflow organization of such works formed the basis for the further development of the project using the latest IT-technologies. For the creation of the second and the third versions of the catalog, the list of objects was obtained as a result of total digitizing of plates and their image processing. The final third version contains 19.5 million stars and galaxies with the maximum possible for the photographic astrometry accuracy. The collection of plates, obtained in other observatories – participants of the project, are partially safe and can be used for the same astrometric tasks.